E-Voting Information System for the General Election of the Head of the Community with Black Box Testing and Dummy Variable Regression Analysis - Irfan Hadi Putra; Ucuk Darusalam; Ratih Titi Komala Sari (Institute of Computer Science (IOCS), 2021)
General elections are basically still carried out conventionally, namely by using paper media in voting. This will lead to weaknesses in the calculation of votes such as a waste of money and time. This study aims to develop a website-based e-voting information system in the general election for the chairman of the RW which is expected to minimize the weaknesses of conventional elections. This system was developed to make the voting process more efficient and easy to use. This application is designed using the PHP programming language and MySQL database, using the waterfall method. By doing black box testing, it is hoped that the e-voting system can run well functionally without any error, and dummy variable testing to determine the influence of voters in selecting candidates based on graduation rate